1993
DOI: 10.4049/jimmunol.150.7.2584
|View full text |Cite
|
Sign up to set email alerts
|

IL-7 enhances the expression of IL-3 and granulocyte-macrophage-CSF mRNA in activated human T cells by post-transcriptional mechanisms.

Abstract: The stromal derived growth factor IL-7 was studied for its ability to modulate cytokine expression in human T cells. IL-7 alone did not induce IL-3 or granulocyte-macrophage-CSF (GM-CSF) mRNA. However, IL-7 enhanced the Con A-induced IL-3 and GM-CSF mRNA accumulation in a dose-dependent way. mRNA stability studies revealed that the effect of IL-7 was caused by post-transcriptional stabilization of the IL-3 and GM-CSF transcripts. Upon Con A treatment, the IL-3 and GM-CSF mRNA decayed with a t1/2 of approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A second destabilizing element beside the ARE in its 3′-UTR was also identified in the coding region of c-myc (39) and in the 5′-UTR of β-interferon (42). The increase in GM-CSF mRNA levels in T lymphocytes induced by various stimuli is not attributable to enhanced levels of transcription, but rather to a significant increase in mRNA stability (43,44). Iwai and colleagues (45) demonstrated that the stabilizing effect of TPA on mRNA containing the GM-CSF 3′-UTR requires both the AU-rich sequence and an additional region located 100-160 nt upstream of the AU-rich element.…”
mentioning
confidence: 96%
“…A second destabilizing element beside the ARE in its 3′-UTR was also identified in the coding region of c-myc (39) and in the 5′-UTR of β-interferon (42). The increase in GM-CSF mRNA levels in T lymphocytes induced by various stimuli is not attributable to enhanced levels of transcription, but rather to a significant increase in mRNA stability (43,44). Iwai and colleagues (45) demonstrated that the stabilizing effect of TPA on mRNA containing the GM-CSF 3′-UTR requires both the AU-rich sequence and an additional region located 100-160 nt upstream of the AU-rich element.…”
mentioning
confidence: 96%